Impact of Economic and Institutional Factors on the Socio-Economic Growth of Khyber Pakhtunkhwa, Pakistan - Muhammad, Imranullah (2018)
The study explores the impact of perceived political, cultural, religious and economic factors on the perceived economic growth of Khyber Pakhtunkhwa in users of formal and informal financial systems. The study applied survey questionnaire technique to record responses from respondents associated with firms from formal and informal financial institutions to gain insight into perceived political, cultural, religious and economic factors. Sample of 500 respondents is taken for the survey, 369 responded, while 309 were found valid. Diversified themes associated with the study were identified and discussed. The results of the study and its implications brought to light the role of formal and informal financial institutions in the context of strategic orientation. Findings of the study are examined in relation to analysis for users of formal financial system which exhibited a change in perceived economic growth to be accounted to perceived political stability, perceived cultural stability, perceived economic environment and perceived religious affiliation in the users of formal financial system. However, the results of informal financial system revealed a significant impact of perceived cultural stability, perceived economic environment, and perceived political stability. Perceived religious affiliation had an insignificant impact on perceived economic growth. The study concludes that once a strong coherence between political, cultural, religious and economic environment is buildup, the economy of KP will starts flourishing. The study recommends that the Government should take steps to channelize the informal setups in to the main stream of the economy by bringing industrial and taxation reforms so that the fruits from the formal financial system can be capitalized.